1995
DOI: 10.1164/ajrccm.151.2.7842220
|View full text |Cite
|
Sign up to set email alerts
|

Tussive effect of capsaicin in patients with gastroesophageal reflux without cough.

Abstract: The aim of this study was to clarify the influence of gastroesophageal reflux (GER) on cough threshold in patients with digestive symptoms but free from respiratory involvement. Of 57 consecutive subjects referred for 24-h esophageal pH monitoring because of digestive reflux symptoms, 29 patients free from respiratory disorders were studied. They underwent esophageal pH monitoring and manometry, upper gastrointestinal endoscopy, pulmonary function tests, and methacholine and capsaicin challenges. The methachol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 14 publications
4
43
0
2
Order By: Relevance
“…This statement is strongly supported [50] and idiopathic pulmonary fibrosis [51]. The cough reflex is also heightened in extra-pulmonary diseases associated with cough such as gastrooesophageal reflux disease [52] and rhinosinusitis [8]. It is important to appreciate that the cough reflex is in dynamic state of activation and a number of exogenous and endogenous factors may alter the degree of sensitization.…”
Section: The Cough Reflex In Diseasementioning
confidence: 96%
“…This statement is strongly supported [50] and idiopathic pulmonary fibrosis [51]. The cough reflex is also heightened in extra-pulmonary diseases associated with cough such as gastrooesophageal reflux disease [52] and rhinosinusitis [8]. It is important to appreciate that the cough reflex is in dynamic state of activation and a number of exogenous and endogenous factors may alter the degree of sensitization.…”
Section: The Cough Reflex In Diseasementioning
confidence: 96%
“…We have also shown that it is important to standardize the IFR, a factor not considered in the clinical papers involving capsaicin [2,3]. The geometric mean was significantly affected when the IFR was not standardized; the repeatability of the test, thus, becomes irrelevant, when the IFR is not controlled.…”
Section: Discussionmentioning
confidence: 95%
“…In the assessment of patients, a clinically significant change in measurement has to lie beyond the 95% range [9]. Studies on cough receptor sensitivity in adults have described estimates of repeatability using analysis of variance [13,14] or correlation methods [6], whilst other studies using capsaicin have not included repeatability measurements for the laboratory [2,3]. In our study, we have demonstrated that the capsaicin cough challenge test is repeatable for C2, C5 and Cth, if the IFR is constant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations